Long-Term Safety and Effectiveness of Lurasidone in Adolescents and Young Adults With Schizophrenia: Pooled Post-hoc Analyses of Two 12-month Extension Studies. (April 2023) - Calisti, Fabrizio; Tocco, Michael; Mao, Yongcai; Pikalov, Andrei; Goldman, Robert
Abstract: Introduction: Earlier onset of schizophrenia, which occurs more commonly in males, is characterized by greater illness severity, chronicity, and functional impairment with a less favorable prognosis than later-onset schizophrenia. The aim of this pooled analysis was to evaluate the long-term safety and effectiveness of lurasidone in the treatment of schizophrenia in adolescents (13–17 years) and young adults (18–25 years). Methods: The 2 pooled studies used similar designs and outcome measures. Patients (13–25 years) with schizophrenia completed an initial double-blind 6-week trial of lurasidone (40 and 80 mg/d), and (80 and 160 mg/d) in the young adult trial. In the open-label long-term trials, adolescent patients were treated with 20-80 mg/d of lurasidone, and adults were treated with 40–160 mg/d of lurasidone. Efficacy was evaluated based on the Positive and Negative Syndrome Scale (PANSS) and Clinical Global Impression-Severity Scale (CGI-S). Results: The safety population consisted of 306 patients (mean age, 16.2 years; 208 patients (68.0%) who completed 12 months of treatment; 8.2% discontinued by 12 months due to an adverse event. Mean (SD) change in the PANSS total score from extension Baseline to Months 6 and 12 was -11.8 (13.9) and -15.3 (15.0), respectively (OC); and mean (SD) change in the CGI-S score was -0.8 (1.0) and -1.0 (1.1), respectively (OC). The most frequent adverse events were headache (17.6%), anxiety (11.4%), schizophrenia (9.8%), and nausea (9.8). No clinically meaningful changes were observed in weight, metabolic parameters, or prolactin. Conclusions: In adolescents and young adults with schizophrenia, treatment with lurasidone was generally well-tolerated and effective. Long-term treatment was associated with continued reduction in symptoms of schizophrenia. Long-term treatment was associated with minimal effects on weight, metabolic parameters, and prolactin. Funding: Angelini Pharma S.p.A. and Sunovion Pharmaceuticals Inc.